The influence of home and environmental characteristics on 5–18 years old children's health during the COVID-19 pandemic: A cross-sectional study in Iran - Golzarpour, Majid; Santana, Paula; Sajjadi, Homeira; Ghaed Amini Harouni, Gholamreza; Costa, Claudia; Ziapour, Arash; Azizi, Seyed Amar; Akbari, Mehdi; Afrashteh, Sima (Frontiers in Public Health, 2023)
Background: The COVID-19 pandemic has dramatically changed the health and well-being of children. Therefore, this study aimed to investigate the relationship between the home environment and the environmental effects on children's health in Iran. Method: An online survey was conducted among parents of children aged 5 to 18 living in large cities in Iran in 2021. The statistical population of this cross-sectional study was 500 people from families with children between 5 and 18 years old. In this survey, questionnaires on the quality of the home environment, exterior and interior landscapes of homes, and child health were used to investigate the relationship between the home environment and environmental influences on children's health during the COVID-19 pandemic. The t-test and analysis of variance were used in SPSS 24, and the structural equation modeling (SEM) was utilized in AMOS 24 for analyzing the data. Results: The average age of respondents was 37.13±7.20, and that of children was 11.57±3.47. 73.02% of the families were covered by insurance, and 74.08% of them lived in the metropolis. In addition, 65.04% of the families have complied with the restrictions of the quarantine period. 31% of families live in villas, and 55% of them during the COVID-19 pandemic paid more attention to cleaning their homes than before the pandemic. A positive and significant statistical relationship (β=0.414, p<0.001) was observed between the residence environment and child health. Thus, the residence environment variable explained 17.5% of variations in child health. Conclusion: The results showed that the children of the people whose exterior landscape of their home was nature had better health. In addition, the children's health of people whose home landscape was a garden, compared to the other two groups (yard, balcony), had better health. Home gardens are a potential source of health and not necessarily replaced with other natural environments, and providing them along with green space is one of the crucial issues that should be considered.